If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 1) = y + -4 Reorder the terms: 2(1 + y) = y + -4 (1 * 2 + y * 2) = y + -4 (2 + 2y) = y + -4 Reorder the terms: 2 + 2y = -4 + y Solving 2 + 2y = -4 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 2 + 2y + -1y = -4 + y + -1y Combine like terms: 2y + -1y = 1y 2 + 1y = -4 + y + -1y Combine like terms: y + -1y = 0 2 + 1y = -4 + 0 2 + 1y = -4 Add '-2' to each side of the equation. 2 + -2 + 1y = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = -4 + -2 1y = -4 + -2 Combine like terms: -4 + -2 = -6 1y = -6 Divide each side by '1'. y = -6 Simplifying y = -6
| 2+6s=26 | | 9y-13y=-10-14 | | 19-12a=79 | | x^4-x^2-14x+54=0 | | 93.3=13b-10.7 | | 3x+5+4x=5 | | 4a-1=-37 | | g(0)=3x^2-2x | | 3+4x-18= | | 2-5x=3x-14 | | -5(x-4)=0 | | -216+125x^3=0 | | x+x+1+x+2=90 | | 5(r-5)=2(r-4)-4 | | 3a-19=-49 | | 2(x-3)=34 | | 4x-23=3x-5 | | 6x+9-5x=12 | | 42a^4+60a^3=0 | | 5z+7=6(z-2)-4(2z-3) | | -39=6+5t | | 25x+5(x+5)+10(x-9)=3,115 | | 3(x)=18 | | (5x^4)(25x^2)= | | x+(x+2)+(x+4)=-17 | | I-4I= | | 2x-5=-4x-2 | | 3x-1=x+21 | | -x+=7 | | 10s+19=119 | | 9x+14+2x=29 | | -9-2=9x+8-8x |